2014
DOI: 10.1137/130925670
|View full text |Cite
|
Sign up to set email alerts
|

Hypergraphs of Bounded Disjointness

Abstract: A k-uniform hypergraph is s-almost intersecting if every edge is disjoint from exactly s other edges. Gerbner, Lemons, Palmer, Patkós and Szécsi conjectured that for every k, and s > s 0 (k), every k-uniform s-almost intersecting hypergraph has at most (s + 1) 2k−2 k−1 edges. We prove a strengthened version of this conjecture and determine the extremal graphs. We also give some related results and conjectures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…If H is a complete multipartite subgraph of the complement of Kneser(n, k) such that no colour class contains more than p|H| vertices, then |H| ≤ n−1 k−1 . Note that similar, but incomparable, generalisations of the Erdős-Ko-Rado Theorem have recently been explored in [5,4,18]. Theorem 3 is proven in Section 4, since it follows almost directly from our proof of the lower bound on the treewidth of a Kneser graph.…”
Section: Introductionmentioning
confidence: 83%
“…If H is a complete multipartite subgraph of the complement of Kneser(n, k) such that no colour class contains more than p|H| vertices, then |H| ≤ n−1 k−1 . Note that similar, but incomparable, generalisations of the Erdős-Ko-Rado Theorem have recently been explored in [5,4,18]. Theorem 3 is proven in Section 4, since it follows almost directly from our proof of the lower bound on the treewidth of a Kneser graph.…”
Section: Introductionmentioning
confidence: 83%
“…Finally, in Section 4, we consider the range of large p. Using the result of [11] stated above, we know that if C p,q is a submatrix of A k,t of size n × n, then n ≤ (2q − 1) 2t t , and [23] proved a conjecture of [12] and showed that for large enough q and t, the size of a q-almost intersecting family F is bounded by (q + 1) 2t−2 t−1 . Note that this last result refers to q-almost cross intersecting pairs (F, G) in which F = G. Furthermore, the constructions presented in [23], which achieve this bound, do not have a circulant intersection matrix.…”
Section: Our Resultsmentioning
confidence: 99%
“…Finally, in Section 4, we consider the range of large p. Using the result of [8] stated above, we know that if C p,q is a submatrix of A k,t of size n × n, then n ≤ (2q − 1) 2t t , and [18] proved a conjecture of [9] and showed that for a large enough q and t, the size of a q-almost intersecting family F is bounded by (q + 1) 2t−2 t−1 . Note that this last result refers to q-almost cross intersecting pairs (F, G) in which F = G. Furthermore, the constructions presented in [18], which achieve this bound, do not have a circulant intersection matrix.…”
Section: Our Resultsmentioning
confidence: 99%